2008
DOI: 10.1007/s00267-008-9235-y
|View full text |Cite
|
Sign up to set email alerts
|

Key Principles of Community-Based Natural Resource Management: A Synthesis and Interpretation of Identified Effective Approaches for Managing the Commons

Abstract: This article examines recent research on approaches to community-based environmental and natural resource management and reviews the commonalities and differences between these interdisciplinary and multi-stakeholder initiatives. To identify the most effective characteristics of Community-Based Natural Resource Management (CBNRM) I collected a multiplicity of perspectives from research teams and then grouped findings into a matrix of "Organizational Principles" and "Key Characteristics." This matrix was then g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
127
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(134 citation statements)
references
References 29 publications
0
127
0
7
Order By: Relevance
“…The SOS framework outlined here represents such an approach, specifically designed for the historical and cultural context of Amazon forest communities and which provides a potentially robust framework for conservation outside of protected areas in the Amazon. Nevertheless, the success of the SOS approach comes at an unavoidable cost: as various authors (e.g., Brockington et al 2008;Gruber 2010) have noted there are no easy solutions to achieving long-term sustainability, and no short-cuts in the painstaking process of collecting data, constructing informal and formal organizations, and building much needed trust among interested parties. We believe it is a cost worth paying if it increases the sustainability of this globally unique ecosystem and the diverse peoples who call it home.…”
Section: Discussionmentioning
confidence: 99%
“…The SOS framework outlined here represents such an approach, specifically designed for the historical and cultural context of Amazon forest communities and which provides a potentially robust framework for conservation outside of protected areas in the Amazon. Nevertheless, the success of the SOS approach comes at an unavoidable cost: as various authors (e.g., Brockington et al 2008;Gruber 2010) have noted there are no easy solutions to achieving long-term sustainability, and no short-cuts in the painstaking process of collecting data, constructing informal and formal organizations, and building much needed trust among interested parties. We believe it is a cost worth paying if it increases the sustainability of this globally unique ecosystem and the diverse peoples who call it home.…”
Section: Discussionmentioning
confidence: 99%
“…The implications of a cognitive perspective is supported by an increasing amount of literature from around the world that illustrates the importance of collaborative approaches to conservation and natural resource stewardship, including from Africa (Western et al 1994, Child andLyman 2005), Asia (Leeuwis and Pyburn 2002), Eastern Europe (Gruber 2010), and the United States (Daniels and Walker 2001, Child and Lyman 2005, Tilt et al 2005, Ballard et al 2008, Dukes et al 2011. Elinor Ostrom's (1990) Nobel Prize-winning work on commons theory is one of the most powerful and widely accepted examples of the importance of the emergent outcomes of peoples' interaction with their environment.…”
Section: Collaborationmentioning
confidence: 97%
“…The emergence of sustainability as a goal for agriculture and development has stimulated increasing interest in understanding ecological processes within agricultural productivity and reducing negative environmental impacts of agricultural activities (Power & Kenmore, 2002). In spite of the difficult reconciliation of conservation and development objectives (Pollini, 2011), experiences in a variety of countries have shown that participatory approaches to research and development, with innovative modes of interaction and mutual learning among farmers, scientists and technical personnel, can effectively develop sustainable agriculture (Pretty, 2002) and community-based natural resource management (Gruber, 2010).…”
Section: The Trajectory Of the Proambiente Programme: From Rural Commmentioning
confidence: 99%